Spatial distribution and geospatial modeling of potential spread of secondary malaria vectors species in Nigeria using recently collected empirical data. - Adedapo O Adeogun; Ayodele Samuel Babalola; Okoko Okefu Oyale; Tolulope Oyeniyi; Ahmed Omotayo; Romoke Tawakalitu Izekor; Oluwakemi Adetunji; Abiodun Olakiigbe; Olalekan Olagundoye; Monsuru Adebayo Adeleke; Chioma Cynthia Ojianwuna; Adamu Dagona; et al. (PLoS ONE)
In Nigeria, most research and malaria vector control efforts have focused on primary vectors within the Anopheles gambiae complex, with less emphasis on other secondary vectors. Consequently, understudied secondary vectors have demonstrated a proportional and increasing role in transmission. This study utilized geospatial models to understand the potential distribution of anopheline species other than An. gambiae complex (non-gambiae species) in Nigeria. Adult mosquitoes were sampled monthly between 2020 and 2022, with concurrent surveys of larval sites in selected Local Government Areas (LGAs) across 20 States resulting in the collection and identification of over 100,000 Anopheline mosquitoes. Utilizing 23 environmental variables, the model produced maps depicting the potential geographical distribution of four secondary vector species under current climatic conditions. An. funestus, An. coustani, An. maculipalpis, and An. rufipes dominated collections, with other species also present. Most species collected exhibited higher occurrences in the Northern parts of the country, albeit with lower numbers, while they seem confined to fewer locations in the southern parts - with higher densities. An. funestus, An. maculipalpis, and An. rufipes demonstrated a higher potential for wide range expansion compared to An. coustani based on the model. Overall, modeling outputs indicate that non-An. gambiae were expected to exhibit a wide-spread across the country, with their distribution primarily influenced by temperature rather than precipitation-related factors. These models provide research scientists and decision-makers with a baseline for research, monitoring towards establishing management plans for future national mosquito surveillance and control programs in Nigeria.